PEMODELAN MATEMATIKA UNTUK JUMLAH PENYALURAN PEMBIAYAAN MUDARABAH, MUSHARAKAH DAN MURABAHAH TERHADAP TINGKAT RASIO NON PERFORMING FINANCING (NPF) - Wardatus Syarifah; Mubrikatul Mabrurah (LPPM Universitas Bina Bangsa, 2023)
Financing is a very important activity because with financing the main source of income will be obtained and will support the continuity of the bank's business. However, as financing increases, the risk of problematic financing cannot be avoided, meaning that as financing increases, problematic financing will also increase. The purpose of this research is to obtain a mathematical model of the Mudarabah Financing, Musharakah Financing and Murabahah Financing on Non Performing Financing (NPF) at BPRS Bhakti Sumekar Sumenep with the research period 2015-2022, where in that year the NPF level at BPRS Bhakti Sumekar often increased, the number of samples 30 quarterly financial report data from BPRS Bhakti Sumekar Sumenep were used. Therefore, this research uses the Multiple Linear Regression method with the help of the SPSS 25 statistical application. The results of calculations using regression analysis obtained a mathematical model of mudarabah, musharakah and murabahah financing on the level of the Non-Performing Financing ratio, namely Y=-2.174 +1.308E-7X1+ 5.025E-8X2+1.039E-8X3. With a significant level of the mudarabah financing variable (x1) of 0.127 > 0.05 and the musharakah financing variable (x2) of 0.374 > 0.05 and murabahah financing (x3) of 0.001 < 0.05, this shows that mudarabah financing and musharakah financing partially does not have a positive and significant influence on the level of the Non Performing Financing ratio. Meanwhile, murabahah financing partially has a positive and significant influence on the level of the Non Performing Financing ratio